RANCANG BANGUN INFORMATION RETRIEVAL SYSTEM (IRS) KAMUS BAHASA-SUNDA.COM DENGAN METODE VECTOR SPACE MODEL (VSM) - Sujiliani Heristian; Hanggoro Aji Al Kautsar; Asep Sayfulloh (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2019)
Sundanese language is no longer the mother tongue / first language in its own area, but it has become the second language after the Indonesian language. The need for preservation of the Sundanese language in the form of online that can be accessed for its users so it will facilitate the searching of text documents especially sunda documents IRS Software is designed to provide the optimal document search results using VSM method, so users will get fast and accurate search results. The VSM method will weight every document in the database so that the documents have different weights to determine which documents are most similar to queries, the highest-weighted documents are ranked in the search results. The evaluation of IRS search results is done by recall and precision tests. Cosine calculation results known that Document 1 (D1) has the highest level of similarity and then followed by D3 and D2 documents is a point or vector in this space. It proves each query that is given has a different level of closeness to the existing documents, it can be Draw the conclusion dkumen which has a high level of similatas influenced by the given query